Young People's Quality of Life and Construction of Citizenship - Tonon, Graciela. author. aut Link
IX, 58 p.
Keywords: This briefs is dedicated to analyze the relations between quality of life and construction of citizenship of young people in Argentina, considering two specific social scenarios: the community and the university. In the case of community it is important to note that it not imply uniformity, as community means the inclusion of diversity and the achievement of sharing within it, and in the case of university it will be necessary to recognize that as an educational institution the university has expanded his traditional role of production of knowledge, to be an institution of social reference and social support for students. To do this the author will show some of the results of a decade of research in quality of life and young people, using quantitative and qualitative methods.